Platiana cechovskyi sp. nov. from Malaysia, a remarkable new member of Dimini (Elateridae: Dendrometrinae) with strongly serrate antennae - Kundrata, Robin; Sormova, Eliska (Zootaxa, 2018)
Platiana Schimmel, 1993 is a moderately large genus in Dimini endemic to South East Asia. Hitherto only four species of this genus were known from Peninsular Malaysia. Here, we describe and figure Platiana cechovskyi sp. nov. from the Cameron Highlands. This species is characteristic by its relatively small body, dark coloration, and strongly serrate antennae which are rarely encountered in Dimini. An identification key to the Platiana species from Peninsular Malaysia as well as a distribution map for all known species are provided.